Delay reduction of transmission control protocol in WiMAX by prioritizing the acknowledgement packets - Suherman Suherman (MATEC Web of Conferences, 2018)
Transmission Control Protocol (TCP) provides reliable connection by acknowledging every transmitted packet. The faster the acknowledgement (ACK) packet is received, the quicker the next TCP window is sent. Previous study shows that by prioritizing the ACK packet route, the TCP delay for the whole data transmission is reduced. This article utilized the medium access within WiMAX network, which is the scheduler, to prioritize the ACK packet transmission. The NS-2 evaluations with various data rate transmission show that the WiMAX scheduling to prioritize the ACK packet successfully reduces the whole data transmission delay. In average, a thirty-second video duration takes 755 ms faster when prioritized ACK is applied.